MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN MELALUI MEDIA E-BOOK PADA SISWA KELAS II SEKOLAH DASAR - Kadoli, Nurnaningsih I; Husain, Rusmin; Pulukadang, Wiwy T.; Katili, Sukri; Husain, Rustam I. (EDUTECH : Jurnal Inovasi Pendidikan Berbantuan Teknologi, 2025)
The problem studied in this study "Can using this E-Book media improve the ability to read early in class II students at SDN 2 Talaga Jaya? This study was conducted with the aim of improving reading skills through E-Book media in class II students at SDN 2 Talaga Jaya, Gorontalo Regency. The research method used is Classroom Action Research (CAR) using data collection techniques through tests, observations, interviews and documentation with research subjects of class II students as many as 13 people. In the initial observation of 13 students, 11 students (85%) were still lacking in reading early. This improvement was proven by the results of the implementation of class actions in cycle I as many as two meetings and cycle II two meetings. The first meeting in cycle I, the achievement of 13 students in reading early obtained (15%) or 2 students who increased. In cycle I, meeting II, students' reading early obtained (38%) or 5 students increased. Cycle II meeting I, students' initial reading gained (69%) or 9 students experienced an increase. Cycle II meeting II experienced an increase in initial reading to (85%) or 11 students were able to read the beginning well and correctly. The results of the study showed that the use of E-Book media significantly increased the ability to read the beginning of class II students of SDN 2 Talaga Java, Gorontalo Regency. ABSTRAKMasalah yang di kaji dalam penelitian ini “Apakah dengan menggunakan media E-Book ini dapat meningkatkan kemampuan membaca permulaan pada siswa kelas II di SDN 2 Talaga Jaya?”. Penelitian ini di laksanakan dengan tujuan untuk meningkatkan kemampuan membaca melalui media E-Book pada siswa kelas II di SDN 2 Talaga Jaya Kabupaten Gorontalo. Adapun metode penelitian yang di gunakan adalah Penelitian Tindakan Kelas (PTK) menggunakan tehnik pengumpulan data melalui tes, observasi,wawancara dan dokumentasi dengan sabjek penelitian siswa kelas II sebanyak 13 orang. Pada observasi awal dari 13 siswa, 11 siswa ( 85%) masih kurang dalam membaca permulaan. Peningkatan tersebut di buktikan dengan hasil pelaksanaan tindakan kelas siklus I sebanyak dua kali pertemuan dan siklus II dua kali pertemuan. Pertemuan pertama pada siklus I capaian 13 siswa membaca permulaan memperoleh (15%) atau 2 orang siswa yang meningkat. Siklus I pertemuan II membaca permulaan siswa memperoleh (38%) atau 5 orang siswa meningkat. Siklus II pertemuan I membaca permulaan siswa memperoleh (69%) atau 9 orang siswa yang mengalami peningkatan. Siklus II pertemuan II mengalami peningkatan membaca permulaan menjadi (85%) atau 11 orang siswa sudah mampu dalam membaca permulaan dengan baik dan tepat. Hasil penelitian menunjukkan bahwa penggunaan media E-Book secara signifikan meningkatkan kemampuan membaca permulaan pada siswa kelas II SDN 2 Talaga Jaya Kabupaten Gorontalo.